Peran Strategis Praktik Kewirausahaan Dalam Penumbuhan Sikap Entrepreneurship Mahasiswa Program Studi Pendidikan Akuntansi FKIP UMS - Aisya, Novia, Agus Susilo, S.Pd., M.Pd (2017)
Absract: The purpose of this study was know strategic role of entrepreneurship practice to grow the entrepreneurship attitude for Accounting Education Students Muhammadiyah University of Surakarta. The approach this research is qualitative and ethnografi design. The data collecting technique are observation, interview, and documentation. Informant this research are eight of students doing Entrepreneurship Practice Lecture and three of lecturers Entrepreneurship Practice. Based on the survey results revealed that the entrepreneurship attitude grow during students doing Entrepreneurship Practice. Students have optimist attitude during Program of Entrepreneurship Practice. The initiative attitude so that Entrepreneurship Practice through fluently has been growing in students self, achievement motive to get the result to be better has been growing in students self are they want to continue a effort that they can. The leadership spirit start to grow too, it is like students to be brave to do the different appear with innovative and creative of product, they to be brave to take the risk too. Conclution of this research is Entrepreneurship Practice can give for students the provisions to be an entrepreneur and step to decrease the unemployment. Entrepreneurship attitude has been growing in students self.